2017
DOI: 10.3390/vaccines5040031
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle Disease Virus Vectored Bivalent Vaccine against Virulent Infectious Bursal Disease and Newcastle Disease of Chickens

Abstract: Newcastle disease virus (NDV) strain F is a lentogenic vaccine strain used for primary vaccination in day-old chickens against Newcastle disease (ND) in India and Southeast Asian countries. Recombinant NDV-F virus and another recombinant NDV harboring the major capsid protein VP2 gene of a very virulent infectious bursal disease virus (IBDV); namely rNDV-F and rNDV-F/VP2, respectively, were generated using the NDV F strain. The rNDV-F/VP2 virus was slightly attenuated, as compared to the rNDV-F virus, as evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
(42 reference statements)
2
22
0
Order By: Relevance
“…Following vaccination, the recombinant NDV generated an effective humoral immune response against ND and ARV infection. Protection against NDV is primarily by the humoral immune response, as is evidenced by several earlier vaccine studies [17,40,41,42]. Moreover, the anti-σC antibody response generated with the recombinant virus was comparable with the ARV inactivated vaccine.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Following vaccination, the recombinant NDV generated an effective humoral immune response against ND and ARV infection. Protection against NDV is primarily by the humoral immune response, as is evidenced by several earlier vaccine studies [17,40,41,42]. Moreover, the anti-σC antibody response generated with the recombinant virus was comparable with the ARV inactivated vaccine.…”
Section: Discussionmentioning
confidence: 51%
“…Viral vectored vaccines could be an alternate approach to control ARV infection. A number of attenuated poultry vaccine viruses, such as Newcastle disease virus (NDV) [14,15,16,17], fowl pox virus (FPV) [18,19,20], adenovirus [21], herpesvirus of turkeys (HVT) [22,23], infectious laryngotracheitis virus (ILTV) [24,25] and Marek’s disease virus (MDV) [26,27,28] have been genetically modified in order to use them as vaccine vectors for developing combinations of live attenuated vaccines for controlling the diseases of poultry. Among these viruses, NDV is an attractive vaccine vector for both human and animal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Live and inactivated vaccines are widely available for the control of IBD. However, these vaccines have the potential risks of incomplete inactivation and reversion to virulence [ 30 ]. A recent study reported that the homologous recombination between the nVarIBDV and IBDV intermediate vaccine strain increased the pathogenicity of nVarIBDV [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of cell-mediated immunity following IBDV infection is well established31,32 with the localization of bursal mRNA transcription of the pro-inflammatory cytokines IL-1β, IL-6, CXCLi2 and IFN-γ together with downregulation of transcription growth factor-β4. In vivo challenge with vvIBDV UK661 strain upregulated the transcription levels of types I, II and III IFNs as well as IL-18, IL-4 and IL-13 cytokines 33…”
Section: Immune Response Towards Ibdv Infectionmentioning
confidence: 99%